Perekonomian Masyarakat Perkebunan Plasma Kelapa Sawit Jorong Jambak Kecamatan Luhak Nan Duo (2003-2019) - Yosi Septrina Ningsih; Azmi Fitrisia (Jurnal Kronologi, 2020)
This research was motivated by the establishment of a PIR BUN OPHIR Pioneering KPS cooperative in charge of managing oil palm plantations in jorong Jambak, West Pasaman district. Almost all of the Jorong Jambak people are farmers of Oil Palm Plasma Plantations. This plantation experienced ups and downs but in 2003 the Oil Palm Plasma Plantation reached its peak. This is evidenced by the development of the Jorong Jambak community's economy until now. This study aims to look at the Economy of the Community of Palm Oil Plasma Plantation in Jorong Jambak Nagari Koto Baru, Luhak Nan Duo District, West Pasaman Regency (2003-2019). The method used in this study is a historical research method which is divided into 4 stages. First, the heuristic step is to find and collect data. The second stage of source criticism, is divided into two namely external criticism and internal criticism to find the validity of the source under study. Thirdly, the interpretation or analysis of data by summarizing all data in order to obtain a picture based on the formulation of the problem in this study. The four stages of historigrafi, namely the writing of research reports into scientific writing, namely thesis. Based on the results of the study it can be concluded that the Oil Palm Plasma Plantation has grown rapidly since 2003. Besides that, public facilities such as health, education and sports facilities were also built. People's livelihoods began to vary due to the existence of these plantations such as traders, employees, and so forth.